EFFECT OF STEEL FIBERS ON REFRACTORY CASTABLES (Journal of Engineering, 2002)
Reinforcement of refractory castables with steel fibers improves their strength for cracking and spalling and expands the service life.The results show that raising the temperature from 700°C to 900°C causes an increase in porosityand decrease in bulk density for refractory castables. This happens because of decomposition of the hydraulic bond of alumina cement. When the temperature is raised higher than 900°C, ceramic bond is formed as a result of sol dreaction between alumina cement and bauxite aggregate. This leads to reduction of the porosity ar d aincrease in the bulk density. Steel fibers are affected positively in reducing the porosity ardaincreasing the bulk density for refractory castables. This positive effect increases with increasethe fibers contentup to 1.5%. All castable samples have good spalling resistances at all temperatures for different percentage of steel fibers.Improvement of reinforced refractory castables increases with rising temperature of firing, but itwas not possible to raise the temperature above 1000°C because of the oxidation of the steel fibers.